A comparison of the changes in seed germination vigour with prolonged storage time between Hope and Sierra malting barley varieties at Delta Beverages, Kwekwe Maltings. - Mwazha, Milford (Midlands State University, 2018)
To increase the brewing yield and efficiency, malts with high extract values, high enzymatic activities, and good modification are essential. To produce malt that meets these requirements, the barley employed must have minimal post-harvest dormancy and be able to germinate rapidly and uniformly. The aims of this study were to compare the changes in seed germination vigour trends and the general storage stability of two Zimbabwean two-row malting barley varieties (Hope and Sierra) as the post-harvest storage time increased. Two samples of these commercially grown varieties were obtained and stored under room temperature laboratory conditions. At monthly intervals the samples had their germination index and energy determined using SAB Miller standards for malting barley analysis (controlled germination in an incubator at 18oC – 21oC for 72 hours). In addition other quality parameters (nitrogen content, screenings, moisture content, water sensitivity and insect damage index) necessary to assess the storage stability of both varieties were also analyzed on monthly intervals using the same analytical standards as for germination tests. On the basis of the results obtained during the 13 months of post-harvest assessments it was found out that Hope had its Germination Index improving as storage time increased meaning that , the variety’s germination vigour improves with time. By the first month of the research the GI index for Hope was 8.7 and gradually it increased reaching 9.2 by the end of the research period. However on the other hand the seed germination vigour for Sierra gradually diminishes with time as indicated by the weak negative downhill correlation (r value = -0.24). As for other grain quality parameters (including moisture loss, insect damage index, germination energy and screenings) Hope proved to be more stable in storage than Sierra. Thus after considering germination performance and general storage stability it was concluded that Hope is a better malting barley variety than Sierra.